Energetics and protomer communication in the dynamical structure of S100A13 in free and protein-bound states. Issue 11 (23rd July 2016) - Omotuyi, Oi; Ueda, H
Abstract: S100A13 is S100 family of EF-hand-containing calcium-binding protein involved in the secretion of some growth factors and pro-inflammatory cytokines lacking signal peptides. The involvement of S100A13 in cancer progression and inflammatory diseases has been reported. In this study, structures generated during atomistic molecular dynamics simulation were studied. Dynamical network analysis data revealed that native inter-protomer communication network driven principally by vdW interaction ( 550 kj/mol) is altered (Receptor for advanced glycation end products (RAGE) C2- and Fibroblast growth factor (FGF)-1-bound S100A13) or completely abolished (interleukin-1 (IL1)-α- and C2A-p40Syt1-bound S100A13) in protein-bound S100A13 homodimer. Bulk water density (weighted atomic density) around exposed S100A13 homodimer surface explored tends to follow the dynamical network lead as S100A13 homodimer appeared densely solvated in C2A-p40Syt1- and IL1)-α-bound states but not in RAGE C2- and FGF-1-bound biosystems. Furthermore, projection of radius of gyration and root mean square deviation (from native structure) variables of the generated structures along the 3D-free energy surface showed anti-parallel β-sheet proximal to Ca 2+ -binding loops-I/II in most metastable complexes retrieved from energy minima state with strong indications for β-sheet network formation during protein binding. Interaction between S100A13 homodimer and ligand–proteins may be dictated by the strength of vdW and electrostatic interaction with possible involvement of bulk water desolvation in some complexes. All these results strongly suggest that disruption of multiprotein receptor complex can be achieved by designing specific compounds targeting a specific aspect of S100A13/protein interaction; such drugs may have clinical usefulness in blocking angiogenesis, reversing cell proliferation and attenuating inflammatory processes.